Development of Professional Characteristics Development Activities for Nursing Students - Chuengkriangkrai, Benchaporn (Nursing Research and Innovation Journal, 2017)
The research aimed to study the effect of professional characteristics development activities for nursing students. The professional characteristics were nursing ethics consisting of compassion, responsibility, honest, and dedication. The samples were 30 second-year volunteer nursing students of a public nursing educational institute in Bangkok. The research instruments were the assessment form of professional characteristics related to nursing virtue and ethics, and the assessment form of activities arrangement. Data were analyzed by using descriptive statistics such as mean and standard deviation, and pair t-test. The results reveal that 1) The mean scores of professional characteristics related to nursing virtue and ethics in consisting of cognitive and attitude domains were significant differences between before and after participating in the arranged activities at .01 and the mean score of the post-test was higher than the pre-test. 2) The total mean scores of virtue and ethics cognitive domain after participating in the arranged activities that evaluated from the test, the learning record and classroom assessment technique were at the good level. 3) The nursing profession guideline that was stated by students the most was responsibility for the duty of caring for the assigned clients and providing nursing practices with gentleness, respectively. 4) The life style guideline that students identified the most was doing the assigned duty very well and assisting distressed and disadvantaged persons. From this study, the developed activities could be applied to develop virtue and ethics for nursing students studying in every level by adjusting the learning contents to be appropriate for knowledge and experience of students.